1993
DOI: 10.3168/jds.s0022-0302(93)77684-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Clinical Mastitis Among Quarters of the Bovine Udder

Abstract: Clinical mastitis episodes occurring from 1962 through 1991 in the Louisiana State University Dairy Research Herd were studied to determine the distribution of clinical mastitis among quarters of the udder. Data were detailed records of all mastitis episodes that occurred during 1630 Holstein lactations. Incidence of episodes, categorized according to which quarters within a cow were clinical for a given case, were compared with mathematical expectations based upon the assumption that quarters were independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 9 publications
5
27
2
1
Order By: Relevance
“…Although several studies did not show different incidences of clinical mastitis episodes between left and right quarters (Batra et al, 1977;Adkinson et al, 1993), Walsh (1985) reported a different incidence of clinical mastitis between left and right quarters in a herd with a one-sided milking parlour. The higher frequency of right-quarter mastitis episodes was caused by teat impaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies did not show different incidences of clinical mastitis episodes between left and right quarters (Batra et al, 1977;Adkinson et al, 1993), Walsh (1985) reported a different incidence of clinical mastitis between left and right quarters in a herd with a one-sided milking parlour. The higher frequency of right-quarter mastitis episodes was caused by teat impaction.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors found the incidence of clinical mastitis to be higher in rear quarters than in front quarters (Rendel and Sundberg, 1962;Flock and Zeidler, 1969;Grootenhuis, 1975;Batra et al, 1977;Adkinson et al, 1993;Miltenburg et al, 1996;Barkema et al, 1997). Deviation from expectation of observed mastitis incidence on quarter level could be attributed to differences in risk factors with bacterial infections around the teat opening between the quarters of the bovine udder in developing clinical mastitis (Barkema et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This model describes, for example, a situation where the treatment carried out during acute clinical mastitis obliterates mastitis symptoms without resulting in total eradication of the germs from the udder [46], in a proportion p of cases. It was also adapted to the case of clinical mastitis affecting a quarter; other quarters then run a much greater risk of suffering mastitis later than they would have, had no quarter of the udder ever been infected [1]. It was adapted in fact in all cases where there was a possible state change in the udder after clinical mastitis.…”
Section: The Model For the Relationship Between Consecutive Mastitis mentioning
confidence: 99%
“…These risk factors were for the most part demonstrated by adjusting the number of cows observed as having clinical mastitis to a Poisson distribution within the framework of a Generalised Linear Model (GLM) type model [28] including fixed effects or even individual random effects. During these analyses, the authors retained only the clinical cases of mastitis arising a certain number of days after a previous episode of clinical mastitis; this time-lapse varies from 8 [22], 10 [24], 14 [1,4,12], 30 [13,40] to 90 [25] days depending on the author. This selection carried out between the mastitis cases observed is aimed at eluding a possible dependence between consecutive events.…”
Section: Introductionmentioning
confidence: 99%